2021
DOI: 10.1002/glia.24008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of demyelination and neurodegeneration in globoid cell leukodystrophy

Abstract: Globoid cell leukodystrophy (GLD), also known as Krabbe disease, is a lysosomal storage disorder causing extensive demyelination in the central and peripheral nervous systems. GLD is caused by loss‐of‐function mutations in the lysosomal hydrolase, galactosylceramidase (GALC), which catabolizes the myelin sphingolipid galactosylceramide. The pathophysiology of GLD is complex and reflects the expression of GALC in a number of glial and neural cell types in both the central and peripheral nervous systems (CNS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 250 publications
(387 reference statements)
2
19
0
Order By: Relevance
“…71 This lethal neurometabolic disorder is caused by mutations in the lysosomal enzyme galactosylceramidase (GALC); more than 130 mutations were already described. 72 GALC degrades galactosylceramides and sphingolipids, abundant constituents of the myelin membranes. nefficiency of this enzyme leads to the accumulation of galactosylsphingosine or psychosine, a by-product of the GALC catabolism in oligodendrocytes and Schwann cells, causing severe demyelination both in the central (CNC) and peripheral nervous system (PNS).…”
Section: Therapeutic Outcomes In Neurological Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…71 This lethal neurometabolic disorder is caused by mutations in the lysosomal enzyme galactosylceramidase (GALC); more than 130 mutations were already described. 72 GALC degrades galactosylceramides and sphingolipids, abundant constituents of the myelin membranes. nefficiency of this enzyme leads to the accumulation of galactosylsphingosine or psychosine, a by-product of the GALC catabolism in oligodendrocytes and Schwann cells, causing severe demyelination both in the central (CNC) and peripheral nervous system (PNS).…”
Section: Therapeutic Outcomes In Neurological Contextmentioning
confidence: 99%
“…nefficiency of this enzyme leads to the accumulation of galactosylsphingosine or psychosine, a by-product of the GALC catabolism in oligodendrocytes and Schwann cells, causing severe demyelination both in the central (CNC) and peripheral nervous system (PNS). 72 Besides demyelination, a myelin-independent axonopathy also occurs in KD, contributing to its severe neuropathology. Indeed, by using a KD transgenic mouse model (the Twitcher mice), we showed that axonal loss 73 occurs before the onset of demyelination, since we detected fewer axons both in the PNS and in the CNS, and of neurons in dorsal root ganglia (DRG) of Twitcher mice before demyelination events.…”
Section: Therapeutic Outcomes In Neurological Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Krabbe disease begins during active myelination and is characterized by extensive demyelination with relative sparing of the gray matter [ 14 ], oligodendrocytes (OLs) have been regarded as the first and primary cells targeted by the pathology (reviewed in [ 15 ]). This demyelination should secondarily affect neurons, whose degeneration likely contributes significantly to major symptoms of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In Krabbe disease, also known as globoid cell leukodystrophy, mutations in β-galactosylceramidase (GALC), a lysosomal enzyme responsible for the catabolism of myelin galactolipids, lead to the accumulation of its substrates galactocerebroside and psychosine [ 1 ]. Whereas galactocerebroside builds up inside macrophages and microglia giving rise to globoid cells, psychosine accumulates in myelinating glia culminating in demyelination and is therefore considered the main culprit of the disorder.…”
mentioning
confidence: 99%